Violencia de género y perfil del agresor en la región sur del Ecuador - Minga Medina, Karen Valery (2024)
Gender violence is considered an urgent global problem that affects one in 3 women throughout their lives. The objective of the study was to relate the type of violence exercised and its relationship with the profile of the aggressor in the southern region of Ecuador. Additionally, the specific objectives were in charge of characterizing women victims of violence and identifying the type of violence to which they are exposed. The research was methodologically developed through the analytical-quantitative, descriptive, retrospective cross-sectional cohort, non-experimental approach, and with a non-probabilistic sample of 402 people. The information was obtained from the existing database of a research project at the National University of Loja, called “Power asymmetries in gender violence in the southern region of Ecuador.” The results indicated that mestizo, single women with a secondary education level and from rural regions prevail. Furthermore, 3 out of 10 women in the study suffered from verbal and psychological violence. On the other hand, the study showed that 1 in 10 aggressors engage in psychological and verbal violence, especially in those with a history of drug and alcohol abuse. Due to the difficulty of the investigation from the point of view of the aggressor, it is necessary to delve deeper into this topic in order to prevent and establish guidelines for this type of problem